Terai Dalits’ Social Status in Nepal: Struggles and Aspirations - Kafle, Dol Raj (Shikshya Sandesh, 2023)
This study investigates the social status of Terai Dalits in Nepal, a marginalized community facing discrimination for centuries. The study aims to provide an in-depth understanding of the origin, social status, and identity of Terai Dalits. The research follows a qualitative design, relying on various sources including secondary documents, books, journals, and websites. It explores the historical perspectives and feelings of the people, focusing on abstract concepts and definitions. Descriptive and analytical methods are employed, adhering to APA 7th edition citation and referencing guidelines. Terai Dalits in Nepal endure precarious social status characterised by economic deprivation, social ostracisation, and untouchability discrimination. They lack land ownership, struggle for education, and face challenges in accessing government resources and services. Discrimination extends to gender disparities, with Dalit women experiencing greater marginalization. Lingering feudalistic practices in Terai society exacerbate their plight, perpetuating a cycle of inequality. Terai Dalits face multiple obstacles, including limited access to policymaking, linguistic divisions, and class exploitation by local elites. Discrimination from both the state and upper-caste individuals contributes to their social exclusion. Terai Dalits’ social status remains fragile, rooted in historical discrimination and cultural practices. To uplift their status, concerted efforts are required at local, regional, and national levels. Initiatives should aim to eradicate discrimination, promote education, and provide economic opportunities, ultimately fostering a more inclusive and equal society for Terai Dalits in Nepal. A collective liberation movement united across linguistic divisions, could be instrumental in achieving these goals and breaking the cycle of inequality.